2022
DOI: 10.3389/fnut.2022.837066
|View full text |Cite
|
Sign up to set email alerts
|

Higher Consumption of Fruit and Vegetables Is Associated With Lower Worries, Tension and Lack of Joy Across the Lifespan

Abstract: Background and AimsHigher total fruit and vegetable (FV) intakes have been associated with lower perceived stress. However, the relationship of FV intake with domains of perceived stress is unclear. The aim of this cross-sectional study was to explore the relationship between consumption of FV and four perceived stress domains (worries, tension, lack of joy and demands) in a population-based cohort of Australian adults.MethodsParticipants (n = 8,640) were men and women aged ≥25 years from the Australian Diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…While there is not a clear biological mechanism linking breakfast consumption directly to mental health, studies have indicated that a higher intake of fruits and vegetables within the overall diet is associated with reduced odds of experiencing worries, tension, and a lack of joy in adults, independently of other lifestyle factors [ 20 ]. Several nutrient-dense foods such as whole grains, eggs, and dairy products are rich in nutrients involved in mental health, endogenous serotonin production, and mood regulation such as magnesium, calcium, tryptophan [ 47 , 48 ], and choline [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is not a clear biological mechanism linking breakfast consumption directly to mental health, studies have indicated that a higher intake of fruits and vegetables within the overall diet is associated with reduced odds of experiencing worries, tension, and a lack of joy in adults, independently of other lifestyle factors [ 20 ]. Several nutrient-dense foods such as whole grains, eggs, and dairy products are rich in nutrients involved in mental health, endogenous serotonin production, and mood regulation such as magnesium, calcium, tryptophan [ 47 , 48 ], and choline [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies of breakfast consumption in association with mental health are also emerging [ 10 12 ]. In addition to the regularity of breakfast intake, specific foods and the quality of breakfast could be crucial for achieving beneficial effects on mental health [ 10 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Flavone glycosides, their aglycones, and metabolites are commonly in foods of plant origin, major phytochemicals, and necessary for disaster risk reduction [1,2]. Intake of flavonols in the diet is important to improve lifespan through the regulation of the basic physiological metabolism [3,4] and mitochondria quality [5,6]. However, there are many forms of natural flavonoids and their derivatives, and there are still many unknown patterns of their absorption and metabolism within cells.…”
Section: Introductionmentioning
confidence: 99%